Isospin-violating dark matter at liquid noble detectors: new constraints, future projections, and an exploration of target complementarity - Andrew Cheek; Darren D. Price; Ellen M. Sandford (European Physical Journal C: Particles and Fields, 2023)
Abstract There is no known reason that dark matter interactions with the Standard Model should couple to neutrons and protons in the same way. This isospin violation can have large consequences, modifying the sensitivity of existing and future direct detection experimental constraints by orders of magnitude. Previous works in the literature have focused on the zero-momentum limit which has its limitations when extending the analysis to the Non-Relativistic Effective Field Theory basis (NREFT). In this paper, we study isospin violation in a detailed manner, paying specific attention to the experimental setups of liquid noble detectors. We analyse two effective Standard Model gauge invariant models as interesting case studies as well as the more model-independent NREFT operators. This work demonstrates the high degree of complementarity between the target nuclei xenon and argon. Most notably, we show that the Standard Model gauge-invariant formulation of the standard spin-dependent interaction often generates a sizeable response from argon, a target nuclei with zero spin. This work is meant as an update and a useful reference to model builders and experimentalists.